New energy automobile tire self-repairing sealing material adhered with mute cotton
By using a self-healing liquid composed of polyurethane cotton and modified polyurethane adhesive in the self-healing tire sealing material, the problem of poor mechanical properties of the sealing material in the prior art is solved, and better silent cotton adhesion and self-repairing effects are achieved.
Patent Information
- Application Number
- CN202510346317.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-24
- Publication Date
- 2025-04-22
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing self-healing tire sealing materials have poor mechanical performance under dynamic working conditions, resulting in the falling off of silent cotton and affecting the self-healing effect.
Polyurethane cotton is used to bond on the surface of the self-healing solution. The self-healing solution consists of anhydrous ethanol, modified polyurethane adhesive, C5 petroleum resin and modified carbon nanotube filler to achieve self-healing of the material through dynamic covalent bonds.
It improves the mechanical properties and self-repairing effect of self-repair sealing materials, ensures the stable adhesion of silent cotton, and enhances the tire's ability to prevent air leakage and explosion protection after damage.
Smart Images

Figure CN119859481A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of automobile tires, and in particular to a new energy automobile tire self-repairing sealing material with adhered silent cotton. Background Art
[0002] With the rapid development of the new energy vehicle industry, the demand for lightweight, low rolling resistance and quiet performance of tires is increasing. Self-repairing tires are an innovative type of tire. At present, the self-repairing tire technologies of major tire manufacturers are different, but most of them are achieved by attaching a layer of polymer composite materials (in the form of soft solid gel) to the inner wall of the tire to prevent air leakage, explosion and self-repair after the tire is punctured. That is, when the tire is punctured by a sharp object, the polymer composite material quickly repairs the puncture, thereby ensuring that the tire does not leak or burst after being punctured, and ensuring the safe driving of the vehicle without the need for tire repair. In order to reduce driving noise, the industry generally adopts the solution of attaching porous sound-absorbing cotton (silent cotton) to the inner wall of the tire. Traditional adhesives are prone to deformation and aging under dynamic conditions such as tire deformation and alternating temperature and humidity, and have poor mechanical properties, which causes the silent cotton to fall off and affects the self-repair effect. For example, patent CN114456744A discloses a tire self-repairing sealant, tire and tire manufacturing method with adhered silent cotton. The tire self-repairing sealant ensures the processing flow performance during rubber coating and takes into account the adhesion effect of the silent cotton, but the mechanical properties and self-repairing properties of the sealant need to be improved. Summary of the invention
[0003] 1. Technical issues to be resolved In view of the shortcomings of the prior art, the present invention provides a new energy vehicle tire self-repairing sealing material with adhered silent cotton, which has good mechanical properties and self-repairing sealing effect.
[0004] (II) Technical solution To achieve the above-mentioned purpose, the present invention provides the following technical solution: a self-repairing sealing material for new energy vehicle tires with adhered silent cotton, wherein the polyurethane cotton is adhered to the surface of the self-repairing liquid; wherein the self-repairing liquid comprises the following components by weight: 25-30 parts by weight of anhydrous ethanol, 8-12 parts by weight of modified polyurethane adhesive, 2-4 parts by weight of C5 petroleum resin, and 0.4-0.8 parts by weight of modified carbon nanotube filler.
[0005] Preferably, the preparation method of the modified polyurethane adhesive comprises the following steps: (1) Dissolve 3.5-4.3 g of di-2-amino-5-bromophenyl sulfide and 6-8.5 g of diboric acid pinacol ester in 65-85 mL of 1,4-dioxane solvent, add 0.8-1.2 g of catalyst and 7-9 g of potassium carbonate, heat to 100-120° C. under nitrogen atmosphere and reflux for 1.5-3 h. After the reaction is completed, dry by rotary evaporation to obtain a disulfide-bonded borate ester; (2) Add 4.2-5 g of disulfide-containing borate, 8.6-10.4 g of 5-hydroxy-2-naphthaldehyde, and 7.8-10 g of anhydrous magnesium sulfate to 50-90 mL of anhydrous ethanol solvent, and heat to the reaction temperature under a nitrogen atmosphere for 6-10 hours. After the reaction is completed, filter and evaporate to remove the solvent, wash and vacuum dry to obtain a naphthyl-modified disulfide-containing borate modified chain extender; (3) Add 8-12 g of polytetrahydrofuran to the reaction bottle, heat to 110-115°C and perform vacuum dehydration for 1-2 h. After stopping the vacuuming, cool to 50-60°C, add 2.8-3.4 g of toluene diisocyanate and 0.04-0.08 g of dibutyltin dilaurate, introduce nitrogen at 72-85°C and react for 3-4 h. Add 1.2-1.6 g of naphthyl-modified disulfide-containing borate modified chain extender and continue the reaction for 1.5-3 h. After the reaction is completed, a modified polyurethane adhesive is obtained.
[0006] Preferably, the catalyst in step (1) is [1,1-bis(diphenylphosphino)ferrocene]palladium dichloride.
[0007] Preferably, the reaction temperature in step (2) is 65-80°C.
[0008] Preferably, the method for preparing the modified carbon nanotube filler comprises the following steps: S1. Add 3-4.5 g of bis(2-aminophenyl) diselenide, 4.3-5 g of 3-hydroxy-1-adamantyl methacrylate, and 0.03-0.07 g of triethylamine catalyst to 40-60 mL of tetrahydrofuran solvent, stir and mix, and heat to reaction temperature under nitrogen atmosphere for 3-4 h. After the reaction is completed, dry by rotary evaporation to obtain diselenide bond-containing adamantane; S2. Add 1.6-2.8 g of chlorinated multi-walled carbon nanotubes into 150-200 mL of N,N-dimethylformamide solvent, and mix thoroughly by ultrasonic treatment for 3-4 h. Then add 5.6-6.2 g of diselenide bond-containing adamantane, and disperse by ultrasonic treatment for 1.5-2 h. In a nitrogen atmosphere, react at 85-95°C for 18-24 h. After the reaction is completed, filter, wash with deionized water, and vacuum dry to obtain modified carbon nanotube filler.
[0009] In the above reaction process, the amino group in bis(2-aminophenyl) diselenide and the alkenyl group in 3-hydroxy-1-adamantyl methacrylate undergo Michael addition reaction to obtain diselenide bond-containing adamantane and introduce hydroxyl groups, and the hydroxyl groups in the diselenide bond-containing adamantane react with the acyl chloride groups in the acyl chloride multi-walled carbon nanotubes to obtain modified carbon nanotube fillers.
[0010] Preferably, the reaction temperature in S1 is 45-60°C.
[0011] Preferably, the preparation method of the chlorinated multi-walled carbon nanotubes in S2 is: 2-3.5 g of carboxylated multi-walled carbon nanotubes are placed in a reaction bottle, 120-200 mL of thionyl chloride and 8-12 mL of N,N-dimethylformamide are added, and the reaction is refluxed at 70-74°C for 16-22 hours. After the reaction is completed, the unreacted thionyl chloride is removed by rotary evaporation, and the mixture is washed with N,N-dimethylformamide, centrifuged, and vacuum dried to obtain chlorinated multi-walled carbon nanotubes.
[0012] Preferably, the preparation method of the new energy vehicle tire self-repair sealing material with adhered silent cotton is: add 8-12 weight parts of modified polyurethane adhesive, 2-4 weight parts of C5 petroleum resin, and 0.4-0.8 weight parts of modified carbon nanotube filler to 25-30 weight parts of anhydrous ethanol, stir and mix evenly to obtain a self-repairing liquid, adhere the polyurethane cotton on the self-repairing liquid, and dry it at 35-40°C for 10-14h to obtain the new energy vehicle tire self-repair sealing material with adhered silent cotton.
[0013] 3. Beneficial technical effects The invention adds modified polyurethane adhesive, C5 petroleum resin and modified carbon nanotube filler into anhydrous ethanol, stirs and mixes them evenly to obtain a self-repairing liquid, adheres polyurethane cotton on the self-repairing liquid, and obtains a new energy vehicle tire self-repairing sealing material with adhered silent cotton after drying.
[0014] Dynamic covalent bonds are reversible and can break and reform under certain conditions. When a material is damaged and cracks or defects appear, the dynamic covalent bonds located at the cracks or defects will break. Under appropriate external conditions, these broken dynamic covalent bonds can recombine to achieve self-repair of the material. In the modified polyurethane adhesive, the disulfide bond, borate bond and imine bond introduced by the chain extension reaction and the diselenide bond introduced in the modified carbon nanotube filler are all dynamic covalent bonds, thereby improving the self-repairing performance of the self-repairing sealing material; in the modified polyurethane adhesive, the mechanical properties of the self-repairing sealing material are improved by introducing rigid benzene rings and naphthyl aromatic structures; carbon nanotubes have high strength and modulus. When carbon nanotubes are evenly dispersed in polyurethane, they can play the role of skeleton support in the matrix. By introducing the rigid structure of adamantane into carbon nanotubes, the mechanical properties of the self-repairing sealing material are further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is the synthetic reaction formula for the naphthyl-modified disulfide-bond-containing borate-modified chain extender. DETAILED DESCRIPTION Example 1
[0016] (1) 3.5 g of di-2-amino-5-bromophenyl sulfide and 6 g of diboronic acid pinacol ester were dissolved in 65 mL of 1,4-dioxane solvent, and 0.8 g of [1,1-bis(diphenylphosphino)ferrocene] palladium dichloride catalyst and 7 g of potassium carbonate were added thereto. The mixture was heated to 100° C. and refluxed for 1.5 h under a nitrogen atmosphere. After the reaction was completed, the mixture was dried by rotary evaporation to obtain a disulfide-bonded borate ester; (2) Add 4.2 g of disulfide-containing borate, 8.6 g of 5-hydroxy-2-naphthaldehyde, and 7.8 g of anhydrous magnesium sulfate to 50 mL of anhydrous ethanol solvent, and heat to 65 °C for 6 h under a nitrogen atmosphere. After the reaction is completed, filter and evaporate to remove the solvent, wash and vacuum dry to obtain a naphthyl-modified disulfide-containing borate modified chain extender; (3) 8 g of polytetrahydrofuran was added to the reaction bottle, the temperature was raised to 110°C for vacuum dehydration for 1 h, the vacuum was stopped, the temperature was lowered to 50°C, 2.8 g of toluene diisocyanate and 0.04 g of dibutyltin dilaurate were added, nitrogen was introduced at 72°C for reaction for 3 h, 1.2 g of naphthyl-modified disulfide-containing borate modified chain extender was added and the reaction was continued for 1.5 h. After the reaction was completed, a modified polyurethane adhesive was obtained; (4) Add 3 g of bis(2-aminophenyl) diselenide, 4.3 g of 3-hydroxy-1-adamantyl methacrylate, and 0.03 g of triethylamine catalyst to 40 mL of tetrahydrofuran solvent, stir and mix, and heat to 45 °C under nitrogen atmosphere for 3 h. After the reaction, dry by rotary evaporation to obtain diselenide bond-containing adamantane; (5) 2 g of carboxylated multi-walled carbon nanotubes were placed in a reaction bottle, 120 mL of thionyl chloride and 8 mL of N,N-dimethylformamide were added, and the reaction was refluxed at 70 °C for 16 h. After the reaction was completed, the unreacted thionyl chloride was removed by rotary evaporation, and the mixture was washed with N,N-dimethylformamide, centrifuged, and vacuum dried to obtain chlorinated multi-walled carbon nanotubes; (6) Add 1.6 g of chlorinated multi-walled carbon nanotubes to 150 mL of N,N-dimethylformamide solvent, ultrasonicate for 3 h to fully mix, then add 5.6 g of diselenide bond-containing adamantane, ultrasonicate for 1.5 h, react at 85 °C for 18 h under a nitrogen atmosphere, filter after the reaction, wash with deionized water, and vacuum dry to obtain a modified carbon nanotube filler; (7) Add 8 parts by weight of modified polyurethane adhesive, 2 parts by weight of C5 petroleum resin, and 0.4 parts by weight of modified carbon nanotube filler to 25 parts by weight of anhydrous ethanol, stir and mix them evenly to obtain a self-repairing liquid, adhere polyurethane cotton on the self-repairing liquid, and dry at 35°C for 10 hours to obtain a new energy vehicle tire self-repairing sealing material with adhered silent cotton. Example 2
[0017] (1) Dissolve 4.3 g of di-2-amino-5-bromophenyl sulfide and 8.5 g of diboronic acid pinacol ester in 85 mL of 1,4-dioxane solvent, add 1.2 g of [1,1-bis(diphenylphosphino)ferrocene] palladium dichloride catalyst and 9 g of potassium carbonate, heat to 120° C. and reflux for 3 h under nitrogen atmosphere, and after the reaction is completed, dry by rotary evaporation to obtain a disulfide bond-containing borate ester; (2) Add 5 g of disulfide-containing borate, 10.4 g of 5-hydroxy-2-naphthaldehyde, and 10 g of anhydrous magnesium sulfate to 90 mL of anhydrous ethanol solvent, and heat to 80 °C for 10 h under a nitrogen atmosphere. After the reaction is completed, filter and evaporate to remove the solvent, wash and vacuum dry to obtain a naphthyl-modified disulfide-containing borate modified chain extender; (3) Add 12 g of polytetrahydrofuran to the reaction bottle, heat to 115 °C and perform vacuum dehydration for 2 h. After stopping the vacuuming, cool to 60 °C, add 3.4 g of toluene diisocyanate and 0.08 g of dibutyltin dilaurate, introduce nitrogen at 85 °C and react for 4 h. Add 1.6 g of naphthyl-modified disulfide-containing borate modified chain extender and continue the reaction for 3 h. After the reaction is completed, a modified polyurethane adhesive is obtained. (4) Add 4.5 g of bis(2-aminophenyl) diselenide, 5 g of 3-hydroxy-1-adamantyl methacrylate, and 0.07 g of triethylamine catalyst to 60 mL of tetrahydrofuran solvent, stir and mix, and heat to 60 °C under nitrogen atmosphere for 4 h. After the reaction, dry by rotary evaporation to obtain diselenide bond-containing adamantane; (5) 3.5 g of carboxylated multi-walled carbon nanotubes were placed in a reaction bottle, 200 mL of thionyl chloride and 12 mL of N,N-dimethylformamide were added, and the reaction was refluxed at 74 °C for 22 h. After the reaction was completed, the unreacted thionyl chloride was removed by rotary evaporation, and the mixture was washed with N,N-dimethylformamide, centrifuged, and vacuum dried to obtain chlorinated multi-walled carbon nanotubes; (6) Add 2.8 g of chlorinated multi-walled carbon nanotubes into 200 mL of N,N-dimethylformamide solvent, ultrasonicate for 4 h to fully mix, then add 6.2 g of diselenide bond-containing adamantane, ultrasonicate for 2 h, react at 95 °C for 24 h under a nitrogen atmosphere, filter after the reaction, wash with deionized water, and vacuum dry to obtain a modified carbon nanotube filler; (7) Add 12 parts by weight of a modified polyurethane adhesive, 4 parts by weight of a C5 petroleum resin, and 0.8 parts by weight of a modified carbon nanotube filler to 30 parts by weight of anhydrous ethanol, stir and mix them evenly to obtain a self-repairing liquid, adhere polyurethane cotton on the self-repairing liquid, and dry at 40°C for 14 hours to obtain a new energy vehicle tire self-repairing sealing material with adhered silent cotton. Example 3
[0018] (1) 3.9 g of di-2-amino-5-bromophenyl sulfide and 7.2 g of diboronic acid pinacol ester were dissolved in 75 mL of 1,4-dioxane solvent, and 1 g of [1,1-bis(diphenylphosphino)ferrocene] palladium dichloride catalyst and 8 g of potassium carbonate were added thereto. The temperature was raised to 110° C. and refluxed for 2.2 h under a nitrogen atmosphere. After the reaction was completed, the mixture was dried by rotary evaporation to obtain a disulfide-bonded borate ester; (2) Add 4.6 g of disulfide-containing borate, 9.5 g of 5-hydroxy-2-naphthaldehyde, and 8.9 g of anhydrous magnesium sulfate to 70 mL of anhydrous ethanol solvent, and heat to 72 °C for reaction for 8 h under a nitrogen atmosphere. After the reaction is completed, filter and evaporate to remove the solvent, wash and vacuum dry to obtain a naphthyl-modified disulfide-containing borate modified chain extender; (3) Add 10 g of polytetrahydrofuran to the reaction bottle, heat to 112 °C and perform vacuum dehydration for 1.5 h. After stopping the vacuuming, cool to 55 °C, add 3.1 g of toluene diisocyanate and 0.06 g of dibutyltin dilaurate, introduce nitrogen at 78 °C and react for 3.5 h. Add 1.4 g of naphthyl-modified disulfide-containing borate modified chain extender and continue the reaction for 2.3 h. After the reaction is completed, a modified polyurethane adhesive is obtained. (4) Add 3.8 g of bis(2-aminophenyl) diselenide, 4.6 g of 3-hydroxy-1-adamantyl methacrylate, and 0.05 g of triethylamine catalyst to 50 mL of tetrahydrofuran solvent, stir and mix, and heat to 52 °C under nitrogen atmosphere for 3.5 h. After the reaction is completed, dry by rotary evaporation to obtain diselenide bond-containing adamantane; (5) 2.8 g of carboxylated multi-walled carbon nanotubes were placed in a reaction bottle, 160 mL of thionyl chloride and 10 mL of N,N-dimethylformamide were added, and the reaction was refluxed at 72 °C for 19 h. After the reaction was completed, the unreacted thionyl chloride was removed by rotary evaporation, and the mixture was washed with N,N-dimethylformamide, centrifuged, and vacuum dried to obtain chlorinated multi-walled carbon nanotubes; (6) Add 2.2 g of chlorinated multi-walled carbon nanotubes to 175 mL of N,N-dimethylformamide solvent, and mix thoroughly by ultrasonication for 3.5 h. Then add 5.9 g of diselenide-containing adamantane, and disperse by ultrasonication for 1.8 h. In a nitrogen atmosphere, react at 90 °C for 21 h. After the reaction is completed, filter, wash with deionized water, and vacuum dry to obtain a modified carbon nanotube filler. (7) Add 10 parts by weight of a modified polyurethane adhesive, 3 parts by weight of a C5 petroleum resin, and 0.6 parts by weight of a modified carbon nanotube filler to 27 parts by weight of anhydrous ethanol, stir and mix them evenly to obtain a self-repairing liquid, adhere polyurethane cotton to the self-repairing liquid, and dry at 38°C for 12 hours to obtain a new energy vehicle tire self-repairing sealing material with adhered silent cotton. Example 4
[0019] (1) 3.5 g of di-2-amino-5-bromophenyl sulfide and 6 g of diboronic acid pinacol ester were dissolved in 65 mL of 1,4-dioxane solvent, and 0.8 g of [1,1-bis(diphenylphosphino)ferrocene] palladium dichloride catalyst and 7 g of potassium carbonate were added thereto. The mixture was heated to 100° C. and refluxed for 1.5 h under a nitrogen atmosphere. After the reaction was completed, the mixture was dried by rotary evaporation to obtain a disulfide-bonded borate ester; (2) Add 4.2 g of disulfide-containing borate, 8.6 g of 5-hydroxy-2-naphthaldehyde, and 7.8 g of anhydrous magnesium sulfate to 50 mL of anhydrous ethanol solvent, and heat to 65 °C for 6 h under a nitrogen atmosphere. After the reaction is completed, filter and evaporate to remove the solvent, wash and vacuum dry to obtain a naphthyl-modified disulfide-containing borate modified chain extender; (3) 8 g of polytetrahydrofuran was added to the reaction bottle, the temperature was raised to 110°C for vacuum dehydration for 1 h, the vacuum was stopped, the temperature was lowered to 50°C, 2.8 g of toluene diisocyanate and 0.04 g of dibutyltin dilaurate were added, nitrogen was introduced at 72°C for reaction for 3 h, 1.2 g of naphthyl-modified disulfide-containing borate modified chain extender was added and the reaction was continued for 1.5 h. After the reaction was completed, a modified polyurethane adhesive was obtained; (4) Add 4.5 g of bis(2-aminophenyl) diselenide, 5 g of 3-hydroxy-1-adamantyl methacrylate, and 0.07 g of triethylamine catalyst to 60 mL of tetrahydrofuran solvent, stir and mix, and heat to 60 °C under nitrogen atmosphere for 4 h. After the reaction, dry by rotary evaporation to obtain diselenide bond-containing adamantane; (5) 3.5 g of carboxylated multi-walled carbon nanotubes were placed in a reaction bottle, 200 mL of thionyl chloride and 12 mL of N,N-dimethylformamide were added, and the reaction was refluxed at 74 °C for 22 h. After the reaction was completed, the unreacted thionyl chloride was removed by rotary evaporation, and the mixture was washed with N,N-dimethylformamide, centrifuged, and vacuum dried to obtain chlorinated multi-walled carbon nanotubes; (6) Add 2.2 g of chlorinated multi-walled carbon nanotubes to 175 mL of N,N-dimethylformamide solvent, and mix thoroughly by ultrasonication for 3.5 h. Then add 5.9 g of diselenide-containing adamantane, and disperse by ultrasonication for 1.8 h. In a nitrogen atmosphere, react at 90 °C for 21 h. After the reaction is completed, filter, wash with deionized water, and vacuum dry to obtain a modified carbon nanotube filler. (7) Add 10 parts by weight of a modified polyurethane adhesive, 3 parts by weight of a C5 petroleum resin, and 0.6 parts by weight of a modified carbon nanotube filler to 27 parts by weight of anhydrous ethanol, stir and mix them evenly to obtain a self-repairing liquid, adhere polyurethane cotton to the self-repairing liquid, and dry at 38°C for 12 hours to obtain a new energy vehicle tire self-repairing sealing material with adhered silent cotton. Example 5
[0020] (1) Dissolve 4.3 g of di-2-amino-5-bromophenyl sulfide and 8.5 g of diboronic acid pinacol ester in 85 mL of 1,4-dioxane solvent, add 1.2 g of [1,1-bis(diphenylphosphino)ferrocene] palladium dichloride catalyst and 9 g of potassium carbonate, heat to 120° C. and reflux for 3 h under nitrogen atmosphere, and after the reaction is completed, dry by rotary evaporation to obtain a disulfide bond-containing borate ester; (2) Add 5 g of disulfide-containing borate, 10.4 g of 5-hydroxy-2-naphthaldehyde, and 10 g of anhydrous magnesium sulfate to 90 mL of anhydrous ethanol solvent, and heat to 80 °C for 10 h under a nitrogen atmosphere. After the reaction is completed, filter and evaporate to remove the solvent, wash and vacuum dry to obtain a naphthyl-modified disulfide-containing borate modified chain extender; (3) Add 12 g of polytetrahydrofuran to the reaction bottle, heat to 115 °C and perform vacuum dehydration for 2 h. After stopping the vacuuming, cool to 60 °C, add 3.4 g of toluene diisocyanate and 0.08 g of dibutyltin dilaurate, introduce nitrogen at 85 °C and react for 4 h. Add 1.6 g of naphthyl-modified disulfide-containing borate modified chain extender and continue the reaction for 3 h. After the reaction is completed, a modified polyurethane adhesive is obtained. (4) Add 3.8 g of bis(2-aminophenyl) diselenide, 4.6 g of 3-hydroxy-1-adamantyl methacrylate, and 0.05 g of triethylamine catalyst to 50 mL of tetrahydrofuran solvent, stir and mix, and heat to 52 °C under nitrogen atmosphere for 3.5 h. After the reaction is completed, dry by rotary evaporation to obtain diselenide bond-containing adamantane; (5) 2.8 g of carboxylated multi-walled carbon nanotubes were placed in a reaction bottle, 160 mL of thionyl chloride and 10 mL of N,N-dimethylformamide were added, and the reaction was refluxed at 72 °C for 19 h. After the reaction was completed, the unreacted thionyl chloride was removed by rotary evaporation, and the mixture was washed with N,N-dimethylformamide, centrifuged, and vacuum dried to obtain chlorinated multi-walled carbon nanotubes; (6) Add 1.6 g of chlorinated multi-walled carbon nanotubes to 150 mL of N,N-dimethylformamide solvent, ultrasonicate for 3 h to fully mix, then add 5.6 g of diselenide bond-containing adamantane, ultrasonicate for 1.5 h, react at 85 °C for 18 h under a nitrogen atmosphere, filter after the reaction, wash with deionized water, and vacuum dry to obtain a modified carbon nanotube filler; (7) Add 8 parts by weight of modified polyurethane adhesive, 2 parts by weight of C5 petroleum resin, and 0.4 parts by weight of modified carbon nanotube filler to 25 parts by weight of anhydrous ethanol, stir and mix them evenly to obtain a self-repairing liquid, adhere polyurethane cotton on the self-repairing liquid, and dry at 35°C for 10 hours to obtain a new energy vehicle tire self-repairing sealing material with adhered silent cotton.
[0021] Comparative Example 1 The difference between this comparative example and Example 5 is that step (7) does not contain modified polyurethane adhesive.
[0022] Comparative Example 2 The difference between this comparative example and Example 5 is that step (7) does not contain modified carbon nanotube filler.
[0023] The mechanical properties and bonding properties of the self-repairing sealing materials in Examples 1-5 and Comparative Examples 1-2 were tested with reference to GB / T2941-2006 and GB / T30774-2014. The test results are shown in Tables 1 and 2.
[0024] Table 1: Mechanical properties tested.
[0025] project Tensile strength (MPa) Elongation at break (%) Elastic recovery rate (%) Example 1 8.37 966 99.2 Example 2 8.43 970 99.6 Example 3 8.40 968 99.4 Example 4 8.35 964 99.2 Example 5 8.46 973 99.5 Comparative Example 1 5.47 594 82.2 Comparative Example 2 4.96 631 94.3 Table 2: Adhesion performance test.
[0026] project Adhesion strength with rubber (N / m) Adhesion strength to rubber after treatment at 100℃ (N / m) Example 1 764 745 Example 2 766 748 Example 3 762 741 Example 4 765 747 Example 5 768 749 Comparative Example 1 488 412 Comparative Example 2 527 492 It can be seen from Table 1 and Table 2 that the self-repairing sealing materials in Examples 1-5 have better mechanical properties than the self-repairing sealing materials in Comparative Examples 1-2, and can still maintain a high bonding force at high temperatures.
[0027] The self-repairing sealing material samples in Examples 1-5 and Comparative Examples 1-2 were cut in the middle, and then the sections were immediately bonded together, and pressed by hand to make the sections close together, and then placed in a set temperature environment for repair for a specified time, and finally the mechanical properties of the repaired samples were tested using a universal testing machine. The self-repairing rate of the samples was obtained by comparing the tensile stress of the samples before and after the repair. The test results are shown in Table 3.
[0028] Table 3: Self-healing performance test.
[0029] project Self-repair rate at room temperature (%) (25°C, 20h) High temperature self-repair rate (%) (80℃, 10h) Example 1 91.4 96.7 Example 2 92.8 97.0 Example 3 91.7 96.8 Example 4 92.5 97.2 Example 5 91.9 97.1 Comparative Example 1 83.4 89.2 Comparative Example 2 86.7 90.4 It can be seen from Table 3 that the self-repairing sealing materials in Examples 1-5 have better self-repairing properties than the self-repairing sealing materials in Comparative Examples 1-2, and can still maintain a high self-repairing rate at high temperatures.
[0030] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well.
Claims
1. A new energy vehicle tire self-repair sealing material with adhered silent cotton, characterized in that: The polyurethane cotton is attached to the surface of the self-repairing liquid; wherein the self-repairing liquid comprises the following components by weight: 25-30 parts by weight of anhydrous ethanol, 8-12 parts by weight of a modified polyurethane adhesive, 2-4 parts by weight of a C5 petroleum resin, and 0.4-0.8 parts by weight of a modified carbon nanotube filler.
2. The new energy vehicle tire self-repairing sealing material with adhered silent cotton according to claim 1, characterized in that: The preparation method of the modified polyurethane adhesive comprises the following steps: (1) Dissolve 3.5-4.3 g of di-2-amino-5-bromophenyl sulfide and 6-8.5 g of diboric acid pinacol ester in 65-85 mL of 1,4-dioxane solvent, add 0.8-1.2 g of catalyst and 7-9 g of potassium carbonate, heat to 100-120° C. under nitrogen atmosphere and reflux for 1.5-3 h. After the reaction is completed, dry by rotary evaporation to obtain a disulfide-bonded borate ester; (2) Add 4.2-5 g of disulfide-containing borate, 8.6-10.4 g of 5-hydroxy-2-naphthaldehyde, and 7.8-10 g of anhydrous magnesium sulfate to 50-90 mL of anhydrous ethanol solvent, and heat to the reaction temperature under a nitrogen atmosphere for 6-10 hours. After the reaction is completed, filter and evaporate to remove the solvent, wash and vacuum dry to obtain a naphthyl-modified disulfide-containing borate modified chain extender; (3) Add 8-12 g of polytetrahydrofuran to the reaction bottle, heat to 110-115°C and perform vacuum dehydration for 1-2 h. After stopping the vacuuming, cool to 50-60°C, add 2.8-3.4 g of toluene diisocyanate and 0.04-0.08 g of dibutyltin dilaurate, introduce nitrogen at 72-85°C and react for 3-4 h. Add 1.2-1.6 g of naphthyl-modified disulfide-containing borate modified chain extender and continue the reaction for 1.5-3 h. After the reaction is completed, a modified polyurethane adhesive is obtained.
3. The new energy vehicle tire self-repairing sealing material with adhered silent cotton according to claim 2 is characterized in that: The catalyst in step (1) is [1,1-bis(diphenylphosphino)ferrocene]palladium dichloride.
4. The new energy vehicle tire self-repairing sealing material with adhered silent cotton according to claim 2, characterized in that: The reaction temperature in step (2) is 65-80°C.
5. The new energy vehicle tire self-repairing sealing material with adhered silent cotton according to claim 1, characterized in that: The method for preparing the modified carbon nanotube filler comprises the following steps: S1. Add 3-4.5 g of bis(2-aminophenyl) diselenide, 4.3-5 g of 3-hydroxy-1-adamantyl methacrylate, and 0.03-0.07 g of triethylamine catalyst to 40-60 mL of tetrahydrofuran solvent, stir and mix, and heat to reaction temperature under nitrogen atmosphere for 3-4 h. After the reaction is completed, dry by rotary evaporation to obtain diselenide bond-containing adamantane; S2. Add 1.6-2.8 g of chlorinated multi-walled carbon nanotubes into 150-200 mL of N,N-dimethylformamide solvent, and mix thoroughly by ultrasonic treatment for 3-4 h. Then add 5.6-6.2 g of diselenide bond-containing adamantane, and disperse by ultrasonic treatment for 1.5-2 h. In a nitrogen atmosphere, react at 85-95°C for 18-24 h. After the reaction is completed, filter, wash with deionized water, and vacuum dry to obtain modified carbon nanotube filler.
6. The new energy vehicle tire self-repairing sealing material with adhered silent cotton according to claim 5, characterized in that: The reaction temperature in S1 is 45-60°C.
7. The new energy vehicle tire self-repairing sealing material with adhered silent cotton according to claim 5, characterized in that: The preparation method of the chlorinated multi-walled carbon nanotubes in S2 is as follows: 2-3.5 g of carboxylated multi-walled carbon nanotubes are placed in a reaction bottle, 120-200 mL of thionyl chloride and 8-12 mL of N,N-dimethylformamide are added, and the reaction is refluxed at 70-74° C. for 16-22 h. After the reaction is completed, the unreacted thionyl chloride is removed by rotary evaporation, and the mixture is washed with N,N-dimethylformamide, centrifuged, and vacuum dried to obtain chlorinated multi-walled carbon nanotubes.
8. A method for preparing a new energy vehicle tire self-repairing sealing material with adhered silent cotton as described in any one of claims 1 to 7, characterized in that: The preparation method of the new energy vehicle tire self-repair sealing material with adhered silent cotton is as follows: 8-12 parts by weight of modified polyurethane adhesive, 2-4 parts by weight of C5 petroleum resin, and 0.4-0.8 parts by weight of modified carbon nanotube filler are added to 25-30 parts by weight of anhydrous ethanol, and the self-repairing liquid is obtained after stirring and mixing evenly, and the polyurethane cotton is attached on the self-repairing liquid, and the self-repairing sealing material of the new energy vehicle tire with adhered silent cotton is obtained after drying at 35-40°C for 10-14 hours.
Citation Information
Patent Citations
Self-repairing polyurethane containing dynamic thionocarbamate bond and preparation method thereof
CN109942773A
Self-repairing reactive polyurethane hot melt adhesive and preparation method thereof
CN113583617A
Preparation method of polyurethane elastomer and chain extender used by polyurethane elastomer
CN116333248A
Polyurethane coating material as well as preparation method and application thereof
CN117777836A
Preparation method of self-repairing modified polyurethane coating for car cover
CN118638467A
Cited By
High-wear-resistant and corrosion-resistant cable and preparation method thereof
CN120674144A
High abrasion and corrosion resistant cable and method of making same
CN120674144B
Polyurethane foam material and preparation method thereof
CN120988245A
A polyurethane foam and a method for producing the same
CN120988245B